Management Of Lecturer Performance Appraisal In Improving The Academic Quality Of Higher Education (Case Study At The Institute Of Technology And Business Swadharma Jakarta) - Warta, Waska; Wibowo, Agung Hardianto; Sucahyo, Nur (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
: One important factor in increasing resources in higher education is lecturers. As one of the universities, the Swadharma Jakarta Institute of Technology and Business strives to improve the quality of lecturers. Increasing the quality of lecturers is carried out by assessing lecturer performance. Good quality lecturers will result in improving the academic quality of higher education. Assessment is carried out by measuring through lecturer assessment indicators in education and teaching activities, research activities, community service activities and other supporting activities. ITB Swadharma has made various efforts to improve academic quality, including by conducting lecturer performance assessments